2015
DOI: 10.1099/ijsem.0.000478
|View full text |Cite
|
Sign up to set email alerts
|

Kineococcus gypseus sp. nov., isolated from saline sediment

Abstract: A novel Gram-stain-positive, aerobic, motile, non-spore-forming coccus-shaped actinomycete, designated strain YIM 121300 T , was isolated from alkaline sediment in Yuanjiang, Yunnan province, south-west China. Phylogenetic analyses based on the 16S rRNA gene sequence showed that strain YIM 121300 T was affiliated to the genus Kineococcus, and was closely related to Kineococcus aurantiacus IFO 15268 T (97.3 % similarity). 16S rRNA gene sequence similarity to other species of the genus Kineococcus was ,97 %. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…In contrast with this, the genera Kocuria, Kineococcus, and Mycolicibacterium were isolated from five out of the six media used. In the case of Kineococcus spp., there are previous reports on their isolation from a wide diversity of media and their ability to grow on them too, including diluted TSA 0.1× (Liu et al, 2009), the rich starch-casein agar medium (Duangmal et al, 2008;Li et al, 2015), or pure TSA (Xu et al, 2017), which also happens for Mycolicibacterium species, as reported by Nouioui et al (2019). Moreover, Kaewkla and Franco (2013) reported a similar strategy of isolating novel culturable strains from trees by extending incubation times and using diluted media, which resulted in the isolation of a wide diversity of genera and new species, including several Nocardioides, Kribbella, and Amycolatopsis isolates, which have grown preferably in intermediate to low concentrations in the case of the samples from the Tabernas Desert.…”
Section: Simple Culture-based Strategies Rescue Significant Fractionsmentioning
confidence: 99%
“…In contrast with this, the genera Kocuria, Kineococcus, and Mycolicibacterium were isolated from five out of the six media used. In the case of Kineococcus spp., there are previous reports on their isolation from a wide diversity of media and their ability to grow on them too, including diluted TSA 0.1× (Liu et al, 2009), the rich starch-casein agar medium (Duangmal et al, 2008;Li et al, 2015), or pure TSA (Xu et al, 2017), which also happens for Mycolicibacterium species, as reported by Nouioui et al (2019). Moreover, Kaewkla and Franco (2013) reported a similar strategy of isolating novel culturable strains from trees by extending incubation times and using diluted media, which resulted in the isolation of a wide diversity of genera and new species, including several Nocardioides, Kribbella, and Amycolatopsis isolates, which have grown preferably in intermediate to low concentrations in the case of the samples from the Tabernas Desert.…”
Section: Simple Culture-based Strategies Rescue Significant Fractionsmentioning
confidence: 99%
“…Values are percentages of total fatty acids. The FAME profiles of the species other than B12 T strain were taken from Phillips et al (2002), Li et al (2015), and Xu et al (2017).…”
Section: Phylogenetics Of Strain B12 Tmentioning
confidence: 99%
“…The genus Kineococcus, belonging to the family Kineosporiaceae [ 1 ], was first proposed by Yokota et al in 1993 [ 2 ]. At the time of writing, the genus Kineococcus is comprised of 11 species with valid published names ( ) which were isolated from soil [ 2 , 3 , 4 , 5 ], saline environments [ 6 , 7 , 8 ], plants [ 9 , 10 ] and radioactive work areas [ 11 ]. This genus includes species with the ability to grow in a wide range of temperatures [ 5 ] and high salt concentrations [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%